2016
DOI: 10.1109/ted.2016.2610466
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Effect on Structural, Functional, and Device Properties of Flexible ZnO Acoustic Wave Sensors Based on Commercially Available Al Foil

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…There is an increasing trend with the increase of thickness of Al foils. The TCF values for the 50 μm Al foil sample are quite large, but are supported by our previously reported values of ZnO/Al foil SAW devices 25 .…”
Section: Principle and Design Methodology For Achieving High Tcfssupporting
confidence: 87%
See 3 more Smart Citations
“…There is an increasing trend with the increase of thickness of Al foils. The TCF values for the 50 μm Al foil sample are quite large, but are supported by our previously reported values of ZnO/Al foil SAW devices 25 .…”
Section: Principle and Design Methodology For Achieving High Tcfssupporting
confidence: 87%
“… Comparison of TCF readings between ZnO/Al SAWs in this study and ZnO based SAWs on other commonly used substrates reported in literature 16 , 22 , 23 , 25 , 33 39 . …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…The Raman peak around 1150 cm À1 is also observed, which is corresponding to the optical overtone of the ZnO. 17 There is a slight decrease for Raman peaks during the corrosion, due to the deteriorated ZnO crystal quality in the acid/alkali harsh environments, although the changes are not so signicant. The reason may be attributed to that the intensity of Raman peaks reects the nature of crystal bonding quality, which does not change signicantly during the corrosion of ZnO lms.…”
Section: Resultsmentioning
confidence: 95%